Bimodal Therapy for Chronic Subjective Tinnitus: A Randomized Controlled Trial of EMDR and TRT Versus CBT and TRT - Luyten, Tine Roanna; Jacquemin, Laure; Van Looveren, Nancy; Declau, Frank; Fransen, Erik; Cardon, Emilie; De Bodt, Marc; Topsakal, Vedat; Van de Heyning, Paul; Van Rompaey, Vincent; Gilles, Annick (Frontiers in Psychology, 2020)
Introduction To date, guidelines recommend the use of a stepped care approach to treat tinnitus. The current clinical management of tinnitus frequently consists of audiologic interventions and tinnitus retraining therapy (TRT) or cognitive behavioral therapy (CBT). Due to the high heterogeneity of the tinnitus population and comorbidity of tinnitus with insomnia, anxiety, and depression, these interventions may not be sufficient for every patient. The current study aims to determine whether a bimodal therapy for chronic, subjective tinnitus consisting of the combination of TRT and eye movement desensitization reprocessing (EMDR) results in a clinically significant different efficacy in comparison with the prevailing bimodal TRT and CBT therapy. Methods Patients were randomized in two treatment groups. The experimental group received the bimodal therapy TRT/EMDR and the active control group received the bimodal therapy TRT/CBT. Evaluations took place at baseline (T0), at the end of the treatment (T1), and 3 months after therapy (T2). The tinnitus functional index (TFI) was used as primary outcome measurement. Secondary outcome measurements were the visual analog scale of tinnitus loudness (VASLoudness), tinnitus questionnaire (TQ), hospital anxiety and depression scale (HADS), hyperacusis questionnaire (HQ), global perceived effect (GPE), and psychoacoustic measurements. Findings The TFI showed clinically significant improvement in both bimodal therapies (mean decrease 15.1 in TRT/CBT; p < 0.001 vs. 16.2 in TRT/EMDR; p < 0.001). The total score on the TQ, HADS, HQ, and VASLoudness all demonstrated significant decrease after treatment and follow-up (p < 0.001) in the experimental and the active control group. GPE-measurements revealed that more than 80% (i.e., 84% in TRT/CBT vs. 80% in TRT/EMDR) of the patients experienced substantial improvement of tinnitus at follow up. Treatment outcome remained stable after 3 month follow-up and no adverse events were observed. Conclusion Both psychotherapeutic protocols result in a clinically significant improvement for patients with chronic subjective tinnitus. No significant different efficacy was found for the TRT/EMDR treatment compared to the combination of TRT and CBT. Clinical Trial registration ClinicalTrials.gov, ID: NCT03114878. April 14, 2017.